EMPLOYEE ENGAGEMENT: ANTECEDENTS AND CONSEQUENCES - Deepti Sinha; Sachin Sinha; Manisha Shukla (Proceedings on Engineering Sciences)
Employee engagement is the emotional connection and dedication that employees feel towards their organisation. It is a term used to describe how dedicated, enthusiastic and involved employees are towards/with their job and the organisation they work for. Antecedents are the variables that influence and contribute towards employee engagement, while consequences are the outcomes linked with employee engagement. Attrition of intellectual capital, disengagement with work, issues of conflict with students, lack of job satisfaction, etc. in the centres of higher education are becoming a burgeoning problem and constructive employee engagement is seen as the solution to these issues. The present study aims to examine the factors responsible for employee engagement as well as the outcomes that are derived due to effective implementation of employee-engagement practices. Data has been collected from 117 faculty members of higher-education institutions from South India using simple random sampling. Data has been analysed with the help of Excel, SPSS and AMOS, using statistical tools like T-test, ANOVA and SEM. The proposed model reflects strong positive association between antecedent variables like autonomy, rewards and recognitions, and fair and equitable treatment and employee engagement, and job satisfaction, organisational commitment and intention to stay as the outcomes of employee engagement.